2013
DOI: 10.2486/indhealth.2012-0134
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Frequent Work-related Burn and Cut Injuries and Low Back Pain among Commercial Kitchen Workers in Japan

Abstract: This study investigated risk factors for frequent work-related burn and cut injuries and low back pain (LBP) among kitchen workers including personal, work-related and environmental factors. Subjects were 991 kitchen workers in 103 schools, 17 hospitals and nursing homes, and 6 restaurants in central Japan. A cross-sectional survey was carried out using a structured selfadministered questionnaire. Logistic regression models were used to examine associations between frequent injuries/LBP and risk factors. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The subjects in this study were 991 workers aged from 17 to 68 yr old in 126 kitchen facilities, which included 103 primary schools (578 workers, 58.3%), 17 hospitals (343 workers, 34.6%), and 6 restaurants (70 workers, 7.1%) in central Japan. The 126 kitchen facilities were recruited from a list that they were compiled by occupational doctors and researchers of this study, as previously reported 19 , 30 ) . All the schools were public schools, and 81 of them were located in the Chubu region, while 22 were located in the Tokyo metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The subjects in this study were 991 workers aged from 17 to 68 yr old in 126 kitchen facilities, which included 103 primary schools (578 workers, 58.3%), 17 hospitals (343 workers, 34.6%), and 6 restaurants (70 workers, 7.1%) in central Japan. The 126 kitchen facilities were recruited from a list that they were compiled by occupational doctors and researchers of this study, as previously reported 19 , 30 ) . All the schools were public schools, and 81 of them were located in the Chubu region, while 22 were located in the Tokyo metropolitan area.…”
Section: Methodsmentioning
confidence: 99%
“…(≤5 times/>5, ≤10 times/>10, ≤20 times/>20 times). For the burns (+) and cuts (+) those who were injured six times or more in the last year were the frequent group, and they were used to analyze the correlation between each factor and injuries according to Tomita’s study 19 ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More women than men work in the university canteen which is consistent with general statistics that women are more likely to work in a kitchen than men. From previous studies, musculoskeletal pain including low back pain seems to be a problem in women more than men [12] [13]. Subjects whom stand up for long time during food preparation could lead to effects on subjective discomfort among cooks during food preparation [14].…”
Section: Health Effects In Canteen Staffmentioning
confidence: 99%